2018
DOI: 10.3329/dujps.v17i2.39175
|View full text |Cite
|
Sign up to set email alerts
|

Clerodendrum inerme (L.) Gaertn. Extract Exerts Anticancer Activity on Lung Cancer Cells

Abstract: Cancer is the leading cause of death word wide. Recently there are no new drugs for safe and efficient treatment. Clerodendrum inerme (L.) Gaertn. (Verbenaceae) plant is being used by the ethnic people for cancer treatment. In this study, cytotoxic and antiproliferative potential of hydroalcoholic (methanol and water; 70:30 v/v) extract of C. inerme were evaluated. Various anticancer investigations performed like, lung cancer cell A-549 culture, dye exclusion assay, MTT assay, morphological changes and compati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This value was higher than the previous studies that showed ethanol leaves extract and hydroalcoholic aerial parts C. inerme exhibited anti-proliferation and anti-cancer activities on lung cancer cell line with IC 50 values at 15.6 µg/ mL and 259.5 μg/mL, respectively. 25,26 To determine the anti-metastatic effects of the extract, the non-toxic concentrations at 200 and 400 µg/ mL and allowing over 80% cell survival were selected. Cell migration and invasion are important steps for the metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This value was higher than the previous studies that showed ethanol leaves extract and hydroalcoholic aerial parts C. inerme exhibited anti-proliferation and anti-cancer activities on lung cancer cell line with IC 50 values at 15.6 µg/ mL and 259.5 μg/mL, respectively. 25,26 To determine the anti-metastatic effects of the extract, the non-toxic concentrations at 200 and 400 µg/ mL and allowing over 80% cell survival were selected. Cell migration and invasion are important steps for the metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%